A Biological Signature for the Inhibition of Outer Membrane Lipoprotein Biogenesis - Kelly M. Lehman; Hannah C. Smith; Marcin Grabowicz (mBio, 2022)
ABSTRACT The outer membrane (OM) of Gram-negative bacteria is an essential organelle that acts as a formidable barrier to antibiotics. Increasingly prevalent resistance to existing drugs has exacerbated the need for antibiotic discovery efforts targeting the OM. Acylated proteins, known as lipoproteins, are essential in every pathway needed to build the OM. The central role of OM lipoproteins makes their biogenesis a uniquely attractive therapeutic target, but it also complicates in vivo identification of on-pathway inhibitors, as inhibition of OM lipoprotein biogenesis broadly disrupts OM assembly. Here, we use genetics to probe the eight essential proteins involved in OM lipoprotein maturation and trafficking. We define a biological signature consisting of three simple assays that can characteristically identify OM lipoprotein biogenesis defects in vivo. We find that several known chemical inhibitors of OM lipoprotein biogenesis conform to the biological signature. We also examine MAC13243, a proposed inhibitor of OM lipoprotein biogenesis, and find that it fails to conform to the biological signature. Indeed, we demonstrate that MAC13243 activity relies entirely on a target outside of the OM lipoprotein biogenesis pathway. Hence, our signature offers simple tools to easily assess whether antibiotic lead compounds target an essential pathway that is the hub of OM assembly. IMPORTANCE Gram-negative bacteria have an outer membrane, which acts as a protective barrier and excludes many antibiotics. The limited number of antibiotics active against Gram-negative bacteria, along with rising rates of antibiotic resistance, highlights the need for efficient antibiotic discovery efforts. Unfortunately, finding the target of lead compounds, especially ones targeting outer membrane construction, remains difficult. The hub of outer membrane construction is the lipoprotein biogenesis pathway. We show that defects in this pathway result in a signature cellular response that can be used to quickly and accurately validate pathway inhibitors. Indeed, we found that MAC13243, a compound previously proposed to target outer membrane lipoprotein biogenesis, does not fit the signature, and we show that it instead targets an entirely different cellular pathway. Our findings offer a streamlined approach to the discovery and validation of lead antibiotics against a conserved and essential pathway in Gram-negative bacteria.